Managing Urban Environment: Assessing the Role of Planning and Governance in Controlling Urbanization in the City of Amman, Jordan - ARABEYYAT, Abdullah Radwan; ALNSOUR, Jamal Ahmad; L-BAZAIAH, Sakher A. I. A; AL-HABEES, Mahmoud A. (Journal of Environmental Management and Tourism, 2024)
The aim of this paper is to explore gaps in the spatial planning and governance systems that affect the ability of local authorities to manage urbanization in Amman, the capital of Jordan. A qualitative method using in-depth interviews with top managers was adopted to understand urbanization challenges and their relationship with spatial planning and governance systems. Findings reveal that spatial planning and governance systems are unable to manage urbanization effectively. Several planning gaps, such as the inability of the spatial planning system to align with the socio-economic context, the lack of policy instruments that provide practical solutions to urbanization challenges, the mismatch between planning and natural resources, the inefficiency of the land subdivision system, the ineffectiveness of urban growth boundary policy, and the poor performance of the public transportation system, have contributed to this lack of inability. The findings reveal a number of governance gaps, such as lack of coordination and overlapping roles between public authorities, centralization, lack of public participation, and insufficient information, have hindered the ability of public authorities to manage urbanization efficiently. To enhance the urban environment, this study provides important insights for policymakers to improve the overall performance of spatial planning and governance.